Preparation method of nano-copper catalyst for vinyl chloride synthesis reaction as well as product and application of nano-copper catalyst
Nanocopper catalysts were prepared by thermal decomposition of copper oxalate, and the Cu0/Cuδ+ ratio was adjusted, which solved the problem of low stability of copper-based catalysts, and improved the efficiency and stability of vinyl chloride synthesis reaction.
Patent Information
- Application Number
- CN202510039903.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-08
AI Technical Summary
The active components of existing copper-based catalysts are easy to reduce in vinyl chloride synthesis reaction, and have low stability, making it difficult to replace mercury-based catalysts.
Copper oxalate is used as a precursor, mixed with solvent and support at normal temperature and pressure, and then heated in a tube furnace to prepare a nano-copper catalyst, adjust the ratio of Cu0/Cuδ+, and improve the stability of the catalyst.
The stability and activity of the catalyst are improved, the efficiency of vinyl chloride synthesis reaction is enhanced, and the average inactivation rate in the first 50 hours is reduced.
Smart Images

Figure CN119771406A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of vinyl chloride synthesis reaction catalyst preparation, and specifically relates to a preparation method of a nano copper catalyst for vinyl chloride synthesis reaction, a product and an application thereof. Background Art
[0002] As one of the world's five major general-purpose resins, polyvinyl chloride is widely used in various fields. As the synthetic raw material of polyvinyl chloride, its production processes mainly include acetylene method, ethylene method and ethane method. Due to the energy structure characteristics of my country's rich coal, poor oil and little gas, my country's production of vinyl chloride is mainly based on the acetylene method.
[0003] At present, mercury-based catalysts are still used in industry. However, mercury-based catalysts are volatile, harmful to human health and pollute the ecological environment. Since realizing this, researchers have been committed to developing efficient mercury-free catalysts and have made a series of research progress. The research on mercury-free catalysts can be mainly divided into three categories: precious metal catalysts (Au, Ru, Pt), base metal catalysts (Cu, Sn) and heteroatom-doped non-metallic catalysts. Among them, Cu-based catalysts are expected to become a substitute for mercury-based catalysts because of their low cost, easy availability, and potential high initial activity. However, copper-based catalysts have the disadvantage that the active components are easy to reduce, resulting in poor stability. Summary of the invention
[0004] The purpose of this section is to summarize some aspects of embodiments of the present invention and to briefly introduce some preferred embodiments.
[0005] As one aspect of the present invention, the present invention provides a method for preparing a nano copper catalyst for vinyl chloride synthesis reaction, which comprises the following steps: Step 1: Mixing, stirring and drying a precursor, a solvent and a carrier at room temperature and pressure; the precursor includes copper oxalate; Step 2: Place the product obtained in step 1 into a tubular furnace, introduce atmosphere for heating, and keep warm to obtain a nano copper catalyst.
[0006] As a preferred embodiment of the method for preparing the nano copper catalyst for vinyl chloride synthesis reaction of the present invention: the solvent is any one or two of deionized water, ammonia water, ethanol, isopropanol, isobutanol, n-propanol, methanol, cyclohexanone, acetone, ether, ethyl acetate, and dichloromethane; or a mixed ion salt is used as the solvent, including a mixed ion salt of potassium chloride and sodium chloride, a mixed ion salt of lanthanum chloride and sodium chloride, a mixed ion salt of lithium chloride and sodium chloride, and a mixed ion salt of lithium chloride and potassium chloride, and the melting point of the ion salt solvent is controlled to be between 300 and 900 °C. o C.
[0007] As a preferred embodiment of the method for preparing the nano copper catalyst for vinyl chloride synthesis reaction of the present invention: the carrier is activated carbon, and the specific surface area of the activated carbon is 700-2000 m 2 / g.
[0008] As a preferred embodiment of the method for preparing the nano copper catalyst for vinyl chloride synthesis reaction of the present invention, the mass fraction of copper in the nano copper catalyst is 5-15%.
[0009] As a preferred embodiment of the method for preparing the nano copper catalyst for vinyl chloride synthesis reaction described in the present invention: the atmosphere includes any one of N2, Ar, He, Ne, Kr, NH3, O2, H2, and 10% H2 / Ar.
[0010] As a preferred solution of the method for preparing the nano copper catalyst for vinyl chloride synthesis reaction of the present invention: the heating process is to increase the temperature to 300-900° C. at a heating rate of 3-5° C. / min.
[0011] As a preferred solution of the method for preparing the nano copper catalyst for vinyl chloride synthesis reaction of the present invention: the insulation time is 1 to 5 hours.
[0012] The present invention also provides application of the nano copper catalyst prepared by the preparation method of the nano copper catalyst for vinyl chloride synthesis reaction in catalyzing acetylene hydrochlorination reaction.
[0013] Preferably, the temperature of the acetylene hydrochlorination reaction is 160-180 °C.
[0014] Preferably, the conditions for the acetylene hydrochlorination reaction are an acetylene space velocity of 36 to 180 h -1 , V HCl :V C2H2 =1.05~1.2.
[0015] The beneficial effects of the present invention are as follows: compared with the currently reported acetylene hydrochloride copper-based catalysts, which have active components that are easy to reduce and have low stability, the present invention provides a method for in-situ regulating Cu 0 / Cu δ+ The ratio of copper oxalate to copper oxalate is a catalyst preparation strategy that improves catalyst stability. During the thermal decomposition process, copper oxalate produces a large amount of CO2, which makes the copper nanoparticles more dispersed, thereby increasing the active sites and improving the activity of the catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] In order to more clearly illustrate the technical solution of the embodiment of the present invention, the following briefly introduces the drawings required for describing the embodiment, wherein: Figure 1(a) Acetylene conversion rate at different loads; (b) Acetylene conversion rate at different calcination temperatures; (c) Acetylene conversion rate at different reaction temperatures.
[0017] Figure 2 The performance comparison of copper oxalate and copper chloride catalysts.
[0018] Figure 3 For 10% CuC2O4 / AC-900 catalyst, -1 The acetylene conversion rate under . DETAILED DESCRIPTION
[0019] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, the specific implementation methods of the present invention are described in detail below in conjunction with specific embodiments. Embodiment 1
[0020] In the first step, under normal temperature and pressure conditions, add 40 mL of deionized water and 3 mL of ammonia water to a beaker. Under stirring, add 0.269 g of copper oxalate to the beaker. After the copper oxalate is completely dissolved, add 2 g of activated carbon (specific surface area 900~1100m 2 / g), impregnated, and dried. The dried catalyst was placed in an ark, which was placed in a tube furnace, and N2 was introduced. The temperature was increased to 900 °C at a heating rate of 5 °C / min, kept at that temperature for 4 h, and naturally cooled to room temperature to obtain a 5%CuC2O4 / AC-900 catalyst.
[0021] 2 mL of the catalyst obtained in the first step was placed in a fixed-bed reactor for acetylene hydrochlorination. The pipeline was purged with N2 for 30 min, then heated to 180 °C at a heating rate of 5 °C / min, activated with HCl for 40 min, and then heated to 40 °C at a space velocity GHSV(C2H2)=180 h -1 , V HCl :V C2H2 =1.15:1, the reaction was started, and the initial acetylene conversion rate was 41.22%, the vinyl chloride selectivity was 99.9%, and the average deactivation rate in the first 50 hours was 0.14% / h. Embodiment 2
[0022] The operation steps of Example 2 are the same as those of Example 1, except that: under normal temperature and pressure conditions, 40 mL of deionized water and 9 mL of ammonia water are added to a beaker, and 1.101 g of copper oxalate is added to the beaker under stirring. After the copper oxalate is completely dissolved, 2 g of activated carbon is added, impregnated, and dried. The dried catalyst is placed in an ark, the ark is placed in a tube furnace, N2 is introduced, and the temperature is increased to 900 ° C at a heating rate of 5 ° C / min, kept warm for 4 h, and naturally cooled to room temperature to obtain a 15% CuC2O4 / AC-900 catalyst.
[0023] The reaction was carried out in a fixed bed reactor, and the initial conversion rate of acetylene was 59.15%, the selectivity of vinyl chloride was 99.9%, and the average deactivation rate in the first 50 hours was 0.23% / h. Embodiment 3
[0024] In the first step, under normal temperature and pressure conditions, add 40 mL of deionized water and 6 mL of ammonia water to a beaker. Under stirring, add 0.620 g of copper oxalate to the beaker. After the copper oxalate is completely dissolved, add 2 g of activated carbon (specific surface area 900~1100m 2 / g), impregnated, and dried. The dried catalyst was placed in an ark, which was placed in a tube furnace, and N2 was introduced. The temperature was increased to 300 °C at a heating rate of 5 °C / min, kept for 4 h, and naturally cooled to room temperature to obtain a 10% CuC2O4 / AC-300 catalyst.
[0025] 2 mL of the catalyst obtained in the first step was placed in a fixed-bed reactor for acetylene hydrochlorination. The pipeline was purged with N2 for 30 min, then heated to 180 °C at a heating rate of 5 °C / min, activated with HCl for 40 min, and then heated to 40 °C at GHSV (C2H2) = 180 h -1 , V HCl :V C2H2 =1.15, the reaction was started, and the initial acetylene conversion rate was 61.87%, the vinyl chloride selectivity was 99.9%, and the average deactivation rate in the first 50 hours was 0.28% / h. Embodiment 4
[0026] The operation steps of Example 4 are the same as those of Example 3, except that the ark is placed in a tube furnace, N2 is introduced, the temperature is increased to 500°C at a heating rate of 5°C / min, the temperature is kept for 4 h, and the temperature is naturally cooled to room temperature to obtain a 10% CuC2O4 / AC-500 catalyst.
[0027] The reaction was carried out in a fixed bed reactor, and the initial conversion rate of acetylene was 63.17%, the selectivity of vinyl chloride was 99.9%, and the average deactivation rate in the first 50 hours was 0.21% / h. Embodiment 5
[0028] The operation steps of Example 5 are the same as those of Example 3, except that the ark is placed in a tube furnace, N2 is introduced, the temperature is increased to 700°C at a heating rate of 5°C / min, the temperature is kept for 4 h, and the temperature is naturally cooled to room temperature to obtain a 10% CuC2O4 / AC-700 catalyst.
[0029] The reaction was carried out in a fixed bed reactor, and the initial conversion rate of acetylene was 56.66%, the selectivity of vinyl chloride was 99.9%, and the average deactivation rate in the first 50 hours was 0.18% / h. Embodiment 6
[0030] The operation steps of Example 6 are the same as those of Example 3, except that the ark is placed in a tube furnace, N2 is introduced, the temperature is increased to 900°C at a heating rate of 5°C / min, the temperature is kept for 4 h, and the temperature is naturally cooled to room temperature to obtain a 10% CuC2O4 / AC-900 catalyst.
[0031] The reaction was carried out in a fixed bed reactor, and the initial conversion rate of acetylene was 52.43%, the selectivity of vinyl chloride was 99.9%, and the average deactivation rate in the first 50 hours was 0.03% / h. Embodiment 7
[0032] The operation steps of Example 7 are the same as those of Example 6, except that: 2 mL of the catalyst obtained in the first step was placed in a fixed-bed reactor for acetylene hydrochlorination reaction, the pipeline was first purged with N2 for 30 min, then the temperature was raised to 160 °C at a heating rate of 5 °C / min, HCl was passed for activation for 40 min, and then the catalyst was heated to 40 °C at GHSV (C2H2) = 180 h -1 , V HCl :V C2H2 =1.15, the reaction was started, and the initial acetylene conversion rate was 26.28%, the vinyl chloride selectivity was 99.9%, and the average deactivation rate in the first 50 hours was 0.02% / h. The catalyst after the reaction was named 10%CuC2O4 / AC-160. Embodiment 8
[0033] The operation steps of Example 8 are the same as those of Example 6, except that: 2 mL of the catalyst obtained in the first step was placed in a fixed-bed reactor for acetylene hydrochlorination reaction, the pipeline was first purged with N2 for 30 min, then the temperature was raised to 200 °C at a heating rate of 5 °C / min, HCl was passed for activation for 40 min, and then the HCl was activated at GHSV (C2H2) = 180 h -1 , V HCl :V C2H2 =1.15, the reaction was started, and the initial acetylene conversion rate was 67.69%, the vinyl chloride selectivity was 99.9%, and the average deactivation rate in the first 50 hours was 0.66% / h. The catalyst after the reaction was named 10%CuC2O4 / AC-200. Embodiment 9
[0034] In the first step, under normal temperature and pressure conditions, add 40 mL of deionized water and 6 mL of ammonia water to a beaker, add 0.620 g of copper oxalate to the beaker while stirring, and after the copper oxalate is completely dissolved, add 2 g of activated carbon, impregnate, and dry. The dried catalyst is placed in an ark, which is placed in a tube furnace, N2 is introduced, and the temperature is raised to 900 °C at a heating rate of 5 °C / min, kept for 4 h, and naturally cooled to room temperature to obtain a 10% CuC2O4 / AC-900 catalyst.
[0035] 2 mL of the catalyst obtained in the first step was placed in a fixed-bed reactor for acetylene hydrochlorination. The pipeline was purged with N2 for 30 min, then heated to 180 °C at a heating rate of 5 °C / min, activated with HCl for 40 min, and then heated to 40 °C at GHSV (C2H2) = 36 h. -1 , V HCl :V C2H2 =1.15, the reaction was started, and the initial acetylene conversion rate was 85.82%, the vinyl chloride selectivity was 99.9%, and the average deactivation rate in the first 50 hours was 0.016% / h.
[0036] Comparative Example 1: In the first step, under normal temperature and pressure conditions, add 40 mL of deionized water to a beaker, add 0.728 g of copper chloride to the beaker while stirring, and after the copper chloride is completely dissolved, add 2 g of activated carbon, impregnate, and dry. The dried catalyst is placed in an ark, which is placed in a tubular furnace, N2 is introduced, and the temperature is raised to 900 °C at a heating rate of 5 °C / min, kept for 4 h, and naturally cooled to room temperature to obtain a 10% CuCl2 / AC-900 catalyst.
[0037] 2 mL of the catalyst obtained in the first step was placed in a fixed-bed reactor for acetylene hydrochlorination. The pipeline was purged with N2 for 30 min, then heated to 180 °C at a heating rate of 5 °C / min, activated with HCl for 40 min, and then heated to 40 °C at GHSV (C2H2) = 180 h -1 , V HCl :V C2H2 =1.15, the reaction was started, and the initial acetylene conversion rate was 26.07%, the vinyl chloride selectivity was 99.9%, and the average deactivation rate in the first 50 hours was 0.13% / h.
[0038] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention may be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should all be included in the scope of the claims of the present invention.
Claims
1. A method for preparing a nano copper catalyst for vinyl chloride synthesis reaction, characterized in that: The following steps are included: Step 1: Mixing, stirring and drying a precursor, a solvent and a carrier at room temperature and pressure; the precursor includes copper oxalate; Step 2: Place the product obtained in step 1 into a tubular furnace, introduce atmosphere for heating, and keep warm to obtain a nano copper catalyst.
2. The method for preparing the nano copper catalyst for vinyl chloride synthesis reaction according to claim 1, characterized in that: The solvent is any one or two of deionized water, ammonia water, ethanol, isopropanol, isobutanol, n-propanol, methanol, cyclohexanone, acetone, ether, ethyl acetate, and dichloromethane; or a mixed ion salt is used as the solvent, including a mixed ion salt of potassium chloride and sodium chloride, a mixed ion salt of lanthanum chloride and sodium chloride, a mixed ion salt of lithium chloride and sodium chloride, and a mixed ion salt of lithium chloride and potassium chloride, and the melting point of the ion salt solvent is controlled to be between 300 and 900 o C.
3. The method for preparing the nano copper catalyst for vinyl chloride synthesis reaction according to claim 1 or 2, characterized in that: The carrier is activated carbon, and the specific surface area of the activated carbon is 700-2000 m 2 / g.
4. The method for preparing a nano copper catalyst for vinyl chloride synthesis reaction according to claim 1 or 2, characterized in that: The mass fraction of copper in the nano-copper catalyst is 5~15%.
5. The method for preparing a nano copper catalyst for vinyl chloride synthesis reaction according to claim 1 or 2, characterized in that: The atmosphere includes any one of N2, Ar, He, Ne, Kr, NH3, O2, H2, and 10% H2 / Ar.
6. The method for preparing the nano copper catalyst for vinyl chloride synthesis reaction according to claim 1 or 2, characterized in that: The heating process is to increase the temperature to 300-900° C. at a heating rate of 3-5° C. / min.
7. The method for preparing the nano copper catalyst for vinyl chloride synthesis reaction according to claim 6, characterized in that: The insulation time is 1 to 5 hours.
8. Use of the nano copper catalyst prepared by the method for preparing the nano copper catalyst for vinyl chloride synthesis reaction according to claim 1 in catalyzing acetylene hydrochlorination reaction.
9. The use according to claim 8, characterized in that: The temperature of the acetylene hydrochlorination reaction is 160-180°C.
10. The use according to claim 9, characterized in that: The conditions for the acetylene hydrochlorination reaction are an acetylene space velocity of 36 to 180 h -1 , V HCl :V C2H2 =1.05~1.2.
Citation Information
Patent Citations
Method for improving performance of non-noble metal catalyst in preparing chloroethylene monomers by hydrochlorination of acetylene
CN107952453A
Low-ruthenium content ruthenium-based catalyst for acetylene hydrochlorination
CN109331869A
Preparing method of copper oxide / carbon nanofiber flexible compound coal gas desulfurizer
CN109999626A
Nanomaterial modified copper-based supported acetylene hydrochlorination catalyst and preparation method thereof
CN110368936A
Medium-low-temperature supported nano copper oxide particle catalyst as well as preparation method and application thereof
CN111558372A